News criteria of South American newspapers. Media treatment about the role of UNASUR in the Venezuelan conflict (March 2014) - Alaniz, María (2015)
The text presents the informative treatment of the regional press regarding statements and the role of the Union of South American Nations (USAN) in the socio-political conflict occurring in Venezuela in March 2014. First and foremost USAN and its creation as an organism which strengthens regional integration bonds are described. Thereafter, considering the media role in making important matters visible for the society and the configuration of perceptions and senses given to them news criteria used in the following newspapers are being analyzed: El Universal (Venezuela), El Tiempo (Colombia), El Comercio (Ecuador) and El Peruano (Peru).